1984
DOI: 10.2135/cropsci1984.0011183x002400020029x
|View full text |Cite
|
Sign up to set email alerts
|

Response of a Maize Synthetic to Recurrent Selection for Stalk Quality1

Abstract: Recurrent selection, based on S1 lines in replicated experiments, was used in separate trials for three cycles to improve the maize (Zea mays L.) synthetic BS1 for resistance to artificial stalk rot (Diplodia maydis) and resistance to mechanical stalk breakage. The cycle populations (BS1 and C1 to C3 for BS1SR and BS1MS for stalk‐rot and stalk‐strength selection, respectively), populations crossed to a low‐stalk‐quality single cross, and crosses of populations between each procedure of selection were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…A inoculação para avaliação da podridão do colmo passou a ser amplamente utilizada em programas de melhoramento de milho (Hooker, 1957), principalmente no estudo da herança da resistência (BeMiller & Pappelis, 1965;Kappelman & Thompson, 1966;Pappelis, 1970;Martin & Russell, 1984a;Martin & Russell, 1984b;Kang et al, 1986;Munkvold & Carlton, 1997). Existe uma correlação positiva entre os dados obti ¶dos pela inoculação de colmos de milho e os obtidos pela infecção natural dos mesmos (Pappelis, 1970).…”
Section: Introductionunclassified
“…A inoculação para avaliação da podridão do colmo passou a ser amplamente utilizada em programas de melhoramento de milho (Hooker, 1957), principalmente no estudo da herança da resistência (BeMiller & Pappelis, 1965;Kappelman & Thompson, 1966;Pappelis, 1970;Martin & Russell, 1984a;Martin & Russell, 1984b;Kang et al, 1986;Munkvold & Carlton, 1997). Existe uma correlação positiva entre os dados obti ¶dos pela inoculação de colmos de milho e os obtidos pela infecção natural dos mesmos (Pappelis, 1970).…”
Section: Introductionunclassified
“…Since then, many approaches to stalk lodging have been explored. Some of these have included bending tests, rind penetration, and anatomical measurements (Davis and Crane, 1976; Martin and Russell, 1984; Zuber et al, 1980). However, the genetic relationships for these methods have proven to be weak to moderate (Flint‐Garcia et al, 2003a,b,c; Peiffer et al, 2013; Hu et al, 2013).…”
mentioning
confidence: 99%
“…have suggested correlations between other morphological traits (e.g., stalk diameter, length of the lower internodes, and number of internodes above the ear) and stalk lodging (Pickett et al, 1969;Martin and Russell, 1984a;Fu et al, 2011). However, Helms and Compton (1984), Martin and Russell (1984b), and Dudley (1994) found that stalk lodging resistance in maize cultivars was only marginally related to the indicators of plant and ear height, the number and length of internodes by recurrent selection for rind strength, and stalk rot resistance.…”
mentioning
confidence: 99%